Epidemiology and Resistance Pattern In Microbial Pneumonia: A Review: Epidemiology and Resistance Pattern in Microbial Pneumonia - Naveed Adil, Muhammad; Royaidar, Jawad; Wadie Yassa, Ramy Rafaat; GonzagaLeong-on, Ma. Socorro; Iqbal, Faisal; Hussain, Abrar; Ali, Qamreen; Rasheed, Arsalan (Pakistan Journal of Health Sciences, 2022)
The pneumonia is a significant public health issue because it raises the mortality and morbidity in people of all ages (2.56 million deaths worldwide each year) and has high medical and financial expenses. The two types of pneumonia i.e. community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP). The incidences of multi-drug resistance in gram negative bacteria create difficulty in treatment and have negative effect on patients’ results. Antimicrobial resistance has also increased with passage of time. The goal of the current study was to describe microbial pneumonia with a focus on the pathogens’ etiology, pathogenicity, epidemiology, resistance pathways, diagnosis updates, and vaccine issues in order to address the issue before it has serious consequences. When choosing an antibiotic medication, clinicians face a significant challenge due to the emergence of novel illnesses, the increase in bacteria with multiple medication resistance, and germs that are challenging to cure. It is demonstrated that the effectiveness of first antimicrobial treatment is a critical issue for mortality in pneumonia, it is imperative to manage and effectively guide adequate antibiotic treatment. This requires the knowledge of engagement of the numerous pathogens in etiology of pneumonia. Additionally, until microbiological data are known and prompt de-escalation cannot be conducted; broad-spectrum antibiotic therapy may occasionally be administered. An overview of the epidemiology, resistance trends, microbiological etiology, and microbial diagnostics of pneumonia is given in this review.